Inter-villages Sentiments: Decentralization on Nias Island, Indonesia - Damanik, Erond Litno (International Journal of Psychosocial Rehabilitation, 2020)
This paper is an attempt to explore and discuss the decentralization on Nias Island, North Sumatra Province, Indonesia. The problem is focused on strengthening inter-village sentiment that has an impact on district separation and the election of regional executives. The theoretical reference used is the construction of ethnicity as tools to achieve political power. Data was collected through participatory observation and in-depth interviews with subjects such as regional heads, local politicians, and the community. The phenomenological approach is used to analyze problems. This study concludes that decentralization on Nias Island had an impact on strengthening inter- village sentiments. The sentiment was used for the separation of districts and the election of regional heads. The sentiment is reflected in the bo’o Mbanua, bo’o Mbowo or different villages, different customs. Identity construction creates awareness of each village population that is different from other villages.